2021
DOI: 10.1007/s42844-021-00043-9
|View full text |Cite
|
Sign up to set email alerts
|

Role of Family in Refugee Adjustment: Experiences of Hmong, Somali, and Syrian Refugees in the USA

Abstract: Compared to other immigrants, refugees often face unique challenges and higher levels of trauma due to their abrupt migration. When resettling in a new country, refugees may continue to face trauma, including race-based trauma, which impacts their overall well-being and adjustment. Despite the vast literature on trauma and refugees, few studies have examined the positive role of family in refugee adjustment. Using a qualitative approach, the current study explores the role of family and support from family mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…This suggested that refugee women had limited alternatives to earn money or that they did not receive enough support from other sources. Studies have shown that family members' instrumental support is essential to refugees' adjustment processes [14][15]. For instance, a study conducted among Hmong, Syrian, and Somali refugees in the United States indicated that the financial and educational support from family members helped them settle into their host country [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggested that refugee women had limited alternatives to earn money or that they did not receive enough support from other sources. Studies have shown that family members' instrumental support is essential to refugees' adjustment processes [14][15]. For instance, a study conducted among Hmong, Syrian, and Somali refugees in the United States indicated that the financial and educational support from family members helped them settle into their host country [15].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that family members' instrumental support is essential to refugees' adjustment processes [14][15]. For instance, a study conducted among Hmong, Syrian, and Somali refugees in the United States indicated that the financial and educational support from family members helped them settle into their host country [15]. The material and financial support somewhat alleviated the economic hardships faced by refugee women.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our findings support previous studies highlighting the importance of continuous relationships in families and communities for successful refugee adjustment (cf. Seff et al, 2021;Xiong et al, 2021). Family and community members represented safe continuity in adolescent refugees' lives.…”
Section: Temporality and Need Satisfaction Among Adolescent Refugeesmentioning
confidence: 99%
“…While family dysfunction and conflict are associated with poor mental health outcomes, family social support has consistently emerged as an important source of strength and resilience across studies with diverse refugee populations in different resettlement contexts [12,20]. Qualitative research with Hmong, Syrian, and Somali refugees in the United States, for instance, found that family social support, sense of belonging in the family, family centrality, and ethnic community as an extension of the family played an integral role in coping with resettlement stressors and fostering positive adjustment [21]. These findings supporting the vital role of the family in influencing mental health, coping, and adjustment are consistent with a family systems perspective, which views the family as a dynamic system that is both impacted by stressful social contexts as well as a potential source of resilience [22].…”
Section: Introductionmentioning
confidence: 99%